Anoctamin 10‐Related Autosomal Recessive Cerebellar Ataxia: Comprehensive Clinical Phenotyping of an Irish Sibship. Issue 2 (18th July 2016) - Bogdanova‐Mihaylova, Petya; Austin, Neil; Alexander, Michael D.; Cassidy, Lorraine; Early, Anne; Murphy, Raymond P.; Murphy, Sinéad M.; Walsh, Richard A.
Abstract: View Supplementary Video 1 View Supplementary Video 2 The autosomal recessive cerebellar ataxias are a heterogeneous group of neurodegenerative disorders. Mutations in the anoctamin 10 gene ( ANO10 ) recently have been identified as a cause of autosomal recessive spinocerebellar ataxia type 10. Comprehensive phenotypic data are provided on 3 siblings with homozygous ANO10 mutations, including detailed ocular and cognitive assessments and bladder involvement not previously described in the literature. Data also are provided on unblinded therapy with coenzyme Q10, previously reported as a possible therapy in ANO10 ‐related ataxia. A genetic diagnosis in this family was obtained through next‐generation sequencing techniques after over 10 years of expensive sequencing of individual genes using the traditional Sanger approach. Greater commercial availability of gene panels will improve the ability to obtain a genetic diagnosis in the uncommon "non‐Friedreich's" recessive ataxias. Clinical recognition of these recessive ataxic syndromes will also inevitably improve as the full phenotypic spectrum is identified. Abstract : View Supplementary Video 1 View Supplementary Video 2